Effect of Balloon Dilatation and Stent Implantation in Iliac Vein Compression Syndrome - Yang, Sen; Zhao, Jian; Hou, Peng; Gu, Yan (The Thoracic and Cardiovascular Surgeon, 2025)
Objective To investigate the efficacy of balloon dilatation combined with stent implantation in the treatment of iliac vein compression syndrome (IVCS).Methods This research was a retrospective study that enrolled 127 IVCS patients for clinical data. The patients were divided into percutaneous transluminal angioplasty (PTA) group (n = 63) and stent implantation group (n = 64). The PTA group was treated with iliac vein balloon dilatation, and the stent implantation group was treated with combined stent implantation based on the PTA group. In both the groups, the quality of life was assessed using Chronic Venous Insufficiency Quality of Life Questionnaire (CIVIQ); complications occurring during the perioperative period and at postoperative follow-up were recorded; the vascular patency rate was calculated, and patient's condition was evaluated using the Villalta scale.Results The stent implantation group exhibited lower postoperative CIVIQ scores than the PTA group, and the stent implantation group (4.60%) had lower complication rate than the PTA group (19.05%). At 2 years of follow-up, the stent implantation group (92.19%) had higher vascular patency rate than the PTA group (79.37%). Villalta scores were lower in the stent implantation group than in the PTA group at 6, 12, and 24 months postoperatively.Conclusion Iliac vein balloon dilatation combined with stent implantation for the treatment of IVCS can improve vessel patency rates, alleviate patients' clinical symptoms, and enhance their quality of life.
Keywords: iliac vein compression syndrome; balloon dilatation; stent implantation; endovascular therapy; venous diseases; prognosis